A new species of Onobrychis sect. Onobrychis (Fabaceae) from Iran - Ranjbar, Massoud; Askari, Ali; Karamian, Roya; Joharchi, Mohmad Reza; Tolui, Zeinab (Phytotaxa, 2018)
Onobrychis farimanensis is described as a new species and an identification key, illustrations and distribution map provided. The new species is restricted to the north Zharf Mountains between Fariman and Torbat-e Heydarieh, in the Khorasan Razavi Province of Iran. It is a perennial herb, becoming woody at the base and has long wing petals, standard as long as the keel, and pods loosely covered by appressed hairs. The new species differs from morphologically similar taxa, O. alamutensis and O. major, in several morphological characters such as plant height, stem indumentum, leaflet length and indumentum, bract length, calyx length, corolla colour, and pod size and shape.